Abdominal impact study on paediatric cadaveric subjects. (2015) - Ouyang, Jun; Zhu, Qingan; Zhong, Shizhen; Li, Zeyu; Liu, Chang
The purpose of this study was to provide structural response of front abdominal impact in children. Nine unembalmed cadavers were divided into two groups. A young cohort aged 2-4 years (four cadavers) and an older cohort aged 5-12 years (five cadavers) were impacted. An autopsy was performed after the impact. The average velocity of the cadaveric tests was 6.3 m/s (±0.25 m/s). Mean peak V*C values were 2.53±0.59 m/s and 1.98±0.41 m/s in old cadaveric cohort and young cadaveric cohort respectively (p > 0.05). The maximum deformation and mean peak forces were 9.27±0.21 cm, 530.30±102.62 N and 9.88±1.50 cm, 929.16±133.24 N in young cohort and old cohort separately (p < 0.05). Eight cadavers were found with various injuries. Good force-deformation data may be derived from the cadaveric response data, and force/deformation corridors have been derived for both subject populations.